Örgütlü suçluluk ve cürüm işlemek için teşekkül kurma suçu (TCK m.313) - Meşe, Mehmet (My University, 2004)
Günümüz ceza hukukunun üzerinde tartıştığı ve sınırlarını tam olarak belirleyemediği konulardan biri de Örgütlü Suçluluktur. Şu kadar var ki; örgütlü suçluluk bir üst kavramdır ve bunun kapsamına Terör Örgütü, Organize Suç Örgütü ve Sınır Aşan Suç Örgütü gibi örgütler dahil olmaktadır. Bunlardan terör örgütü, siyasal düzeni değiştirmeye yönelik örgüt olduğu halde; organize suç örgütü, daha çok haksız kazanç sağlama etrafında birleşmiş üyelerden oluşan birleşmeyi ifade etmektedir. Sınır aşan suç örgütü ise, örgütlü suçluluğun küreselleşmeyle birlikte ulusal sınırları aşarak uluslararası bir görünüm sonucu ortaya çıkan suçluluğu ifade etmektedir. Örgütlü suçluluğun diğer bir türü ise, bu tür suçluluğun ceza hukukunda en eski düzenlemelerinde birini yansıtan Cürüm İşlemek İçin Teşekkül Kurma Suçu oluşturmaktadır. Bu suç, mevcut Türk Ceza Kanunu'nun 313. maddesinde düzenlenmiş olup, 5237 Sayılı Türk Ceza Kanunu'nda ise, Suç İşlemek İçin Örgüt Kurma başlığı altında ve madde 220'de düzenlenmiştir. GENERAL INFORMATIONS Name and Surname : Mehmet Meşe Mainscience Branch : Law Branch of Science : Public law Supervisor : Doc. Dr. Ahmet Gokcen Degree Awarded and Date : Master- December 2004 Organized Guiltiness, Establishing Organisation to Commit Crime

One of the subjects that the crime law of our day discusses on and can not determine the limits properly is Organised Guiltiness. But; the organised guiltiness is an upper term and includes the Terror Organisation, the Organised Crime Organisation, the Organisation That Exceeds The Boundries and such organisations. Among those; while terror organisation is the organisation that intends to alter the political instituition, the organised crime organisation expresses the union that is established by the members who came together for providing unjust gain. And the organisation that exceeds the boundries expresses the guitiness that came up with as the result of the international type of the organised crime that exceeded the national boundries and came up with globalisation. One another type of the organised crime is the guilt of Establishing an Organisation to Commit Crimes that reflects one of the oldest regulations of that kind of guiltiness in the law of crime. That guilt has been regulated in the 313. item of the existing Turkish Crime Law and has been regulated in the 5237 numbered Turkish Crime Law under the topic of Establishing an Organisation to Commit Crimes and in the 220. item.
Keywords: Anayasa ve idare hukuku; Hukuk; Kamu Hukuku